2008
DOI: 10.1182/blood-2007-06-098061
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of the histone deacetylase inhibitor vorinostat (suberoylanilide hydroxamic acid [SAHA]) in patients with advanced leukemias and myelodysplastic syndromes

Abstract: Vorinostat (suberoylanilide hydroxamic acid, SAHA) is a histone deacetylase inhibitor active clinically in cutaneous T-cell lymphoma and preclinically in leukemia. A phase 1 study was conducted to evaluate the safety and activity of oral vorinostat 100 to 300 mg twice or thrice daily for 14 days followed by 1-week rest. Patients with relapsed or refractory leukemias or myelodysplastic syndromes (MDS) and untreated patients who were not candidates for chemotherapy were eligible. Of 41 patients, 31 had acute mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
341
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(356 citation statements)
references
References 44 publications
15
341
0
Order By: Relevance
“…Phase I-II clinical trials are underway or have been recently performed with SAHA in patients with advanced hematological malignancies, including MM [6][7][8][9][10][11][12][13]. Overall, these studies showed that SAHA was tolerable, although its toxicity profile was not negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I-II clinical trials are underway or have been recently performed with SAHA in patients with advanced hematological malignancies, including MM [6][7][8][9][10][11][12][13]. Overall, these studies showed that SAHA was tolerable, although its toxicity profile was not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…One class of HDACIs is the hydroxamate derivatives family of compounds whose prototype is suberoyl anilide hydroxamic acid (SAHA) [5], which is being tested clinically in several hematological malignancies and has obtained FDA approval for the treatment of cutaneous T-cell lymphoma [6][7][8][9][10][11][12][13][14][15]. Our group has recently reported that ITF2357, an orally effective member of the family of hydroxamate-derived HDACIs, is a potent inducer of apoptosis and death of MM cells in vitro [16].…”
Section: Introductionmentioning
confidence: 99%
“…Let-7 family members also target HMGA2, an oncogene known for its involvement in promoting the epithelial-mesenchymal transition (EMT) (Shell et al, 2007). miR-15 and miR-16 promote apoptosis by suppressing expression of the antiapoptotic Bcl-2 protein and are commonly deleted in chronic lymphocytic leukemia (CLL), which leads to high levels of Bcl-2 expression (a prognostic indicator in CLL) (Volinia et al, 2006;Garcia-Manero et al, 2008). miR34a has been shown in multiple studies to be regulated by the frequently mutated/deleted gatekeeper gene, p53.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of histone-modifying enzymes will be another potential epigenetic target for MDS therapy. There are HDIs currently in clinical trials; however, less data is available for their use in MDS, though anecdotal responses have been reported [75]. Recently, it has also been reported that DNA methylation per se is not a permanent lock for silencing gene expression, but rather a combination of DNA methylation inhibitors with other drugs (such as HDIs) can be used to reactivate gene expression [76,77].…”
Section: Epigenetic Therapymentioning
confidence: 99%